TEACHER STRATEGIES IN IMPROVING THE SOCIO-EMOTIONAL DEVELOPMENT OF 4-5 YEAR-OLD CHILDREN THROUGH BLOCK PLAY AT AISYIYAH BUSTANUL ATHFAL LINDUK PRESCHOOL - Satriyah Triyastati; Mahsiani Mina Laili; Vina Karina Putri; Umalihayati; Inten Risna (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study was motivated by the importance of early childhood social-emotional development as the foundation for character building and interpersonal skills in the future. However, there are still children aged 4-5 years who experience difficulties in interacting with their peers and expressing their emotions appropriately. This study aims to describe and analyze the strategies used by teachers to enhance the social-emotional development of 4- to 5-year-old children through block play at the Aisyiyah Bustanul Athfal Linduk Early Childhood Education Center. The method used is qualitative with a descriptive approach, employing data collection techniques such as observation, interviews, and documentation. This study involved 1 teacher and 5 children aged 4-5 years (Class A). The results of the study indicate that the teacher's strategies in enhancing the social-emotional development of 4-5-year-old children through block play at PAUD Aisyiyah Bustanul Athfal Linduk include several approaches such as fostering polite behavior, collaborative small-group learning, varied teaching methods, and managing children's emotions during block play. These strategies successfully stimulated children's social-emotional aspects, including cooperation, empathy, independence, and self-control. In this case, the active role of teachers as facilitators and companions in block play is very important, and block play contributes significantly to children's social-emotional development at the PAUD